2022
DOI: 10.1108/nfs-11-2021-0331
|View full text |Cite
|
Sign up to set email alerts
|

Eating behavior among remote working adults during the COVID-19 pandemic

Abstract: Purpose The Malaysian movement control order is a series of national lockdowns implemented by the Malaysian federal government to contain the spread of Coronavirus disease-2019 (COVID-19). The government has made it mandatory for all non-essential sectors to work remotely to mitigate the spread of COVID-19. The eating behavior of working adults may have altered following the changes in working norms. This study aimed to assess the eating behavior of remote working adults during the COVID-19 pandemic. Design/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…Those restrictions of movement and prolonged stays at home encouraged increased consumption of “ tasty ” food and snacks and food ordering from restaurants [ 10 ]. This aligns with studies pointing out that people's eating behavior was altered during the COVID-19 pandemic [ 11 , 12 ]. In situations of anxiety or negative stress, people prefer to consume hedonically rewarding foods, that is, foods high in sugar and fat [ 13 ].…”
Section: Introductionsupporting
confidence: 90%
“…Those restrictions of movement and prolonged stays at home encouraged increased consumption of “ tasty ” food and snacks and food ordering from restaurants [ 10 ]. This aligns with studies pointing out that people's eating behavior was altered during the COVID-19 pandemic [ 11 , 12 ]. In situations of anxiety or negative stress, people prefer to consume hedonically rewarding foods, that is, foods high in sugar and fat [ 13 ].…”
Section: Introductionsupporting
confidence: 90%
“…Since then, several COVID-19 outbreaks have been reported in various regions of Malaysia. To curb the spread of this disease, the Malaysian government implemented different phases of lockdown in stages over the past year [ 4 ]. This causes unprecedented disruption to all sectors.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals in social isolation cared more about daily food intake and took more precautions in food intake (al Amin et al , 2021). Although many people began to cook meals at home (Alhusseini and Alqahtani, 2020; Sidor and Rzymski, 2020), others chose to consume restaurant food (Tan et al , 2022). In the present study, about one-third of the participants who observed total isolation increased their consumption of food delivery.…”
Section: Discussionmentioning
confidence: 99%